2015
DOI: 10.3389/fnhum.2015.00066
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of cardiovascular fitness are associated with better executive function and prefrontal oxygenation in younger and older women

Abstract: Aim: Many studies have suggested that physical exercise training improves cognition and more selectively executive functions. There is a growing interest to clarify the neurophysiological mechanisms that underlie this effect. The aim of the current study was to evaluate the neurophysiological changes in cerebral oxygenation associated with physical fitness level and executive functions.Method: In this study, 22 younger and 36 older women underwent a maximal graded continuous test (i.e., trueV˙O2max) in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
171
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 75 publications
23
171
2
Order By: Relevance
“…Our findings are in line with Dupuy et al (2015), who found that higher-fit individuals who demonstrate better cardiorespiratory functions show faster reaction times and greater cerebral oxygenation. Similarly, our results align with Prakash et al (2011), who reported a greater blood oxygen level-dependent (BOLD) signal increases in the prefrontal cortex during the Executive Stroop conditions for individuals who demonstrated a higher cardiorespiratory function.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in line with Dupuy et al (2015), who found that higher-fit individuals who demonstrate better cardiorespiratory functions show faster reaction times and greater cerebral oxygenation. Similarly, our results align with Prakash et al (2011), who reported a greater blood oxygen level-dependent (BOLD) signal increases in the prefrontal cortex during the Executive Stroop conditions for individuals who demonstrated a higher cardiorespiratory function.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, the relationship between aerobic fitness level and level of EF was found to be mediated by frontal lateralization (i.e., compensatory neural recruitment) in older adults24 in accordance with the hemispheric asymmetry reduction in older adults (HAROLD) model2526. Dupuy, et al 27. found significant positive associations among physical fitness, frontal brain oxygenation, and EF, suggesting, in accordance with previous studies, that a higher level of cardiorespiratory fitness is related to higher task-evoked hemodynamic responses in frontal areas.…”
supporting
confidence: 80%
“…The pattern of results reported in these cross-sectional studies supports the argument that PA influences cognition through its effects on the functional allocation of neural resources (i.e., functional activation) during cognitive tasks. The results of several other cross-sectional studies assessing links between fitness, neural functioning, and cognition provide support for this general idea (Dupuy et al, 2015; Gauthier et al, 2015). However, these studies did not fully test for mediation because they either did not observe or did not test for the prerequisite correlations amongst the variables.…”
Section: Level 2: Macroscopic Brain Systemsmentioning
confidence: 61%